2014
DOI: 10.1038/tp.2014.90
|View full text |Cite
|
Sign up to set email alerts
|

SLC6A3 coding variant Ala559Val found in two autism probands alters dopamine transporter function and trafficking

Abstract: Emerging evidence associates dysfunction in the dopamine (DA) transporter (DAT) with the pathophysiology of autism spectrum disorder (ASD). The human DAT (hDAT; SLC6A3) rare variant with an Ala to Val substitution at amino acid 559 (hDAT A559V) was previously reported in individuals with bipolar disorder or attention-deficit hyperactivity disorder (ADHD). We have demonstrated that this variant is hyper-phosphorylated at the amino (N)-terminal serine (Ser) residues and promotes an anomalous DA efflux phenotype.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
135
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(146 citation statements)
references
References 93 publications
7
135
0
Order By: Relevance
“…Our efforts originated from identification of the Val559 variant in two male siblings with an ADHD diagnosis (47). Although our starting point concerned efforts to detect rare, functional gene variation impacting DAT expression or function that could contribute to risk for ADHD, the variant has also been detected in a female subject with BPD (48), and in two unrelated males with an ASD diagnosis (49). ADHD and BPD are found at higher incidence in Lack of genotype differences in relative time spent in the center versus the edge of the activity chambers.…”
Section: Discussionmentioning
confidence: 99%
“…Our efforts originated from identification of the Val559 variant in two male siblings with an ADHD diagnosis (47). Although our starting point concerned efforts to detect rare, functional gene variation impacting DAT expression or function that could contribute to risk for ADHD, the variant has also been detected in a female subject with BPD (48), and in two unrelated males with an ASD diagnosis (49). ADHD and BPD are found at higher incidence in Lack of genotype differences in relative time spent in the center versus the edge of the activity chambers.…”
Section: Discussionmentioning
confidence: 99%
“…These authors also observed a decrease in AMPHinduced stimulation of locomotor behavior. Interestingly, AMPH-evoked DA efflux in transfected HEK-293 cells as monitored by amperometry was found to be insensitive to PKCb antagonism, although these inhibitors restored AMPH evoked efflux lost in the ADHD-associated DAT coding variant Val559 (Bowton et al, 2014).…”
Section: +mentioning
confidence: 98%
“…The following sections include a description of some commonly investigated diseases and the putative role of DAT and VMAT (for examples of other diseases such as autism and bipolar disorder, see Grünhage et al, 2000;Nakamura et al, 2010;Bowton et al, 2014;Nguyen et al, 2014).…”
Section: Dopamine Transporter Vesicular Monoaminementioning
confidence: 99%